2013
DOI: 10.1080/09593330.2012.736539
|View full text |Cite
|
Sign up to set email alerts
|

Profile of trace metals accumulation in core sediment from Seine river estuary (docks basin)

Abstract: The Seine is one of the most polluted rivers in Europe with respect to potentially harmful elements. It receives effluents from the upstream Paris urban and industrial area, and also local inputs from the heavily industrialized Rouen and Le Havre regions. The present study deals with this environmental topic and the concentrations of Cd, Ni, Pb, Hg, Zn and Cu were determined in sediment cores collected in the docks basin of Rouen harbour in 2008. The intensity of metal pollution during recent decades was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…In general, Gao et al (2018) indicated the total content of trace elements decreased with depth in sediments cores, and however, in one core, metal contents remained relatively constant. On the other hand, the results of Hamzeh et al (2013) showed that vertical distribution of metal pollution in the past is much higher than in the surface sediment. The above relationships were not identified also in this study.…”
Section: Resultsmentioning
confidence: 93%
“…In general, Gao et al (2018) indicated the total content of trace elements decreased with depth in sediments cores, and however, in one core, metal contents remained relatively constant. On the other hand, the results of Hamzeh et al (2013) showed that vertical distribution of metal pollution in the past is much higher than in the surface sediment. The above relationships were not identified also in this study.…”
Section: Resultsmentioning
confidence: 93%
“…. It is calculated for a specific metal species by dividing the total metal content by the background reference content of trace metals in the Seine River estuary as determined from prehistoric deposits (4000 BP): Cd = 0.22 mg kg −1 , Co = 10 mg kg −1 , Cr = 40 mg kg −1 , Ni = 16 mg kg −1 , Pb = 20 mg kg −1 , and Zn = 60 mg kg −1 with aluminum normalization . This element is known as one of the major elements of clay minerals and is considered as conservative metal: EF=[Me]sample×[Al]sample[Me]background×[Al]background …”
Section: Resultsmentioning
confidence: 99%
“…Mercury was determined by atomic absorption spectrometry using LECO_AMA254 after pyrolysis of approximately 50 mg of sediment sample in a combustion tube at 500°C under an oxygen flow and collection on a gold amalgamator. CRM was also used to assure the quality control of the method .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the study was carried out in highly urbanized areas within the Seine Estuary. The Seine River is also one of the most polluted rivers in Europe with decreasing, but still significant contamination with Hg (Hamzeh et al 2013). The Chausey Islands are on the other hand a remote area with no direct sources of Hg, where seabird exposure is likely to be linked to their marine food.…”
Section: Comparisons In the Seine Estuary And Farther Afieldmentioning
confidence: 99%